Formation of the Cast Iron Coatings Plasma-Sprayed at Different Substrate Temperatures - Jiang, Chao Ping; Xing, Ya Zhe; Chen, Hong; Hao, Jian Min (Applied Mechanics and Materials, 2011)
In this work, three cast iron coatings were produced by atmospheric plasma spraying. During spraying, the surface temperature of three coatings (substrate temperature) was controlled to be averagely 50oC, 180oC and 240oC by changing the processing parameters. X-ray diffraction (XRD) was employed to analyze the phase structure of the starting powder and the coatings. The results showed that the powder was mainly composed of (Fe,Cr)7C3 and martensite and both the spraying processing and the substrate temperature exerted no influence on coating phase structure. An optical microscope (OM) was used to characterize the microstructure of the cross-section and surface of the coatings. It was found that the cross sectional hardness increased with the increase of the substrate temperature due to the improvement in interlamellar bonding.